Solvent-Free Synthesis of Dihydropyrimidinone by Using Molecular Iodine as Catalyst - Fadlan, Arif; Pratama, Landaeta Yolga; Ilfahmi, Yan Alamanda (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2025)
Dihydropyrimidinone with diverse pharmacological activities can be obtained through the multicomponent of Biginelli reactions by heating aldehyde, ethyl acetoacetate and urea/thiourea in ethanol with the addition of hydrochloric acid. However, this reaction is toxic and shows several drawbacks. Further development for Biginelli reaction was conducted by using heterogeneous catalyst, green solvents, and sustainable heating such as microwave or ultrasound. But various obstacles are also found from these strategies. There are still chances to study the Biginelli reaction by using relatively simpler methods and the readily available and environmentally friendly chemicals. Iodine is a mild Lewis acid, easily available at an affordable price, non-toxic, and environmentally friendly. Iodine has been used in various reactions and organic transformations with high efficiency and selectivity. This report aims to study the solventless synthesis of ethyl 6-methyl-2-oxo-4-phenyl-1,2,3,4-tetrahydropyrimidine-5-carboxylate 4 by using molecular iodine. The reaction was studied by mixing benzaldehyde 1 as aromatic aldehyde, urea 2, and β-keto ester in the form of ethyl acetoacetate 3 with and without the addition of ethanol as solvent. The compound 4 (45% yield) was yielded from a solvent-free reaction whereas the use of ethanol gave the product 4 in 50%yield. The IR, NMR spectra, and HRMS analysis were used for the establishment of the structure of product 4. These finding give new perspective in the preparation of dihydropyrimidinone(s).